Sustaining Talent: Reducing Employee Turnover at Tax Authority through Value Proposition and Social Identity - Andy Taufan; Riani Rachmawati (Universitas Airlangga, 2023)
Objective: This study aims to investigate the factors influencing employee shortage in the public sector, specifically centering on employee's intentions to either remain in or leave the institution. It also aims to examine the impact of perceived benefits received by the employees, their fitness within the organization's social group, and their attachment to the institution on their decision. Design/Methods/Approach: This study was carried out on tax authority's staffs through an online survey sent to potential participants and 388 eligible respondents. The data collected was analyzed using Covariance Based Structural Equation Modeling (CB-SEM). Findings: The findings reveal that employee value proposition and social identity negatively and significantly affect turnover intention. Both of them also positively and significantly affect employee engagement. Moreover, employee engagement only mediates the relationship between social identity and turnover intention. Originality/Value: The novelty of this study lies in the simultaneous utilization of employee value proposition and social identity, both influencing turnover intention. Previous studies primarily used social identity as a moderating variable, without combining these two variables, alongside employee engagement as a mediation variable. This study is particularly novel as it analyzes turnover intention among employees in a government institution, whereas prior studies have predominantly focused on the private sector. Practical/Policy implication: Managers should align their Employee Value Proposition (EVP) with employee expectations. They must provide developmental opportunities and supportive work environments, foster a strong social identity, and prioritize initiatives that enhance employee engagement, like meaningful work and recognition. These measures can effectively reduce turnover intentions.